Integrated multi-omics approach reveals a role of ALDH1A1 in lipid metabolism in human colon cancer cells. (1st May 2019) - Charkoftaki, Georgia; Thompson, David C.; Golla, Jaya Prakash; Garcia-Milian, Rolando; Lam, TuKiet T.; Engel, Jasper; Vasiliou, Vasilis
Highlights: Role of the ALDH1A1 gene in colorectal cancer cells. Integrated network analysis of transcriptomics, proteomics and metabolomics. Down-regulation of the Vitamin A (retinol) metabolism caused by ALDH1A1 suppression. Down-regulation of the cholesterol pathway caused by ALDH1A1 suppression.